Potential of Antihypercholesterol Extract of Sempur Fruit Peel (Dillenia serrata) with In Vivo Study on Male White Rats (Rattus novergicus) - Sainal Edi Kamal, et al. (Humanistic Network for Science and Technology (HNST), 2021)
Sempur (Dillenia serrata) is one of the most commonly found local fruits and comes from South Sulawesi. The peculiarity of this sempur fruit is mainly in its refreshing sour taste and attractive fruit color. Phytochemical test of Sempur fruit peel extract contains alkaloids, flavonoids, saponins, polyphenols and triterpenoids. The research objectives are 1). The purpose of this study was to determine the potential of sempur fruit peel (Dillenia serrata) to reduce total cholesterol levels in white rats (Rattus novergicus) and 2). To determine the average value of the decrease in total cholesterol levels in male white rats (Rattus novergicus) after being given sempur fruit peel extract (Dillenia serrata). The research used was Experimental Laboratory which was carried out at the Pharmacognosy-Phytochemical Laboratory and the Pharmacy Biology Laboratory of the Pharmacy Department of the Sandi Karsa Polytechnic. The method used is the induction of Propylthiouracil and the administration of high fat by measuring total cholesterol levels in male white rats with a glucometer and using the maceration extraction method. The 15 male rats used were divided into 5 groups, namely negative control (Na.CMC 1% w/v), Sempur fruit peel extract 0.5% w/v, Sempur fruit peel extract 1% w/v, Sempur fruit peel extract 1.5% w/v and positive control (Simvastatin). Observations on the decrease in total cholesterol levels were carried out 1 day after treatment. The administration of sempur fruit peel extract 0.5% w/v, 1% w/v, and 1.5% w/v gave the effect of reducing total cholesterol levels in male white rats and at a concentration of 1.5% w/v which showed an effect the best for reducing total cholesterol levels in white rats. Based on the results of the paired sample t test with SPSS which shows significantly that the value of sig. (2-tailed) obtained was 0.023